New Insight into the Ground State of FePc: A Diffusion Monte Carlo Study - Tom Ichibha (Nature Portfolio, 2017)
Abstract We have applied DMC to evaluate relative stability of the possible electronic configurations of an isolated FePc under D 4h symmetry, considering some fixed nodes generated from different methods. They predict A 2g ground state consistently, supporting preceding DFT studies, with confidence overcoming the ambiguity about exchange-correlation (XC) functionals. By comparing DMC with several XC, we clarified the importance of the short-range exchange to describe the relative stability. We examined why the predicted A 2g is excluded from possible ground states in the recent ligand field based model. Simplified assumptions made in the superposition model are identified to give unreasonably less energy gain for A 2g when compared with the reality. The state is found to have possible reasons for the stabilization, reducing the occupations from an unstable anti-bonding orbital, avoiding double occupation of a spatially localized orbital, and gaining exchange energy by putting a triplet spin pair in degenerate orbitals.